Contribution to the knowledge of Seychellois Scirtidae (Coleoptera: Scirtoidea) - Ruta, Rafał (Zootaxa, 2008)
Scirtes confinis sp. nov., S. flavohumeralis sp. nov., and S. mahensis sp. nov. are described from the Seychelles Archipelago. Cyphon circumductus Champion, 1924 is synonymized with C. insularius Champion, 1924. Cyphon insularius Champion, 1924, C. biperforatus Champion, 1924, C. mahensis Champion, 1924, and Scirtes seychellensis Champion, 1924 are redescribed and illustrated; lectotypes and paralectotypes of C. insularius and S. seychellensis are designated.